Calculate the Keq for the reaction 2SO3(g)=2SO2(g)+O2(g) given Keq = 85 for 2SO2(g)+O2(g)=2SO3(g)

Expert Answers
justaguide eNotes educator| Certified Educator

For a chemical reaction aA + bB --> cC + dD, the equilibrium constant is Keq = ({C}^c*{D}^d)/({A}^a*{B}^b) where {A}, {B}, {C} and {D} denote the concentration of A, B, C and D resp.

If for the reaction 2SO2(g)+O2(g)-->2SO3(g), Keq = 85

=> 85 = {SO3}^2/({SO2}^2*{O2})

For the reaction 2SO3(g)-->2SO2(g)+O2(g) the equilibrium constant is the inverse of the reverse reaction.

This gives the required equilibrium constant as 1/85 = 0.011

The equilibrium constant for 2SO3(g)-->2SO2(g)+O2(g) is 0.011